2019
DOI: 10.1007/s42379-019-00030-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence and hegemonic masculinity in China: an analysis based on the quantitative research

Abstract: Based on a survey implemented in a county in central China, the researchers found it is common for women to experience gender-based violence, especially violence at the hands of intimate partners. About half of men surveyed reported inflicting physical or sexual violence on their female partners. One in five men reported having raped a partner or non-partner woman. The physical, mental and reproductive health of the female and male respondents were found to be significantly associated with women's victimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In another study on 2,987 women in China, the prevalence of psychological, physical, and sexual violence was 77.7%, 40.2%, and 11%, respectively; additionally, 52% had experienced two or three types of violence in their life (Yuan & Hesketh, 2021). Finally, Wang et al (2019) found the prevalence rate of economic abuse was 36.5% in a sample of 505 participants from Hong Kong.…”
Section: Economic Abusementioning
confidence: 95%
See 1 more Smart Citation
“…In another study on 2,987 women in China, the prevalence of psychological, physical, and sexual violence was 77.7%, 40.2%, and 11%, respectively; additionally, 52% had experienced two or three types of violence in their life (Yuan & Hesketh, 2021). Finally, Wang et al (2019) found the prevalence rate of economic abuse was 36.5% in a sample of 505 participants from Hong Kong.…”
Section: Economic Abusementioning
confidence: 95%
“…While research from the data used for this study has looked at the lifetime prevalence of IPV among women in China, PNG, and Sri Lanka (i.e., Gibbs et al, 2018; Wang et al, 2019) and health outcomes such as depressive symptoms and poor general health, these studies did not look at the association between IPV and depressive symptoms, in conjunction with other aspects of the survivors’ financial circumstances. Given the impact that economic abuse has on the financial capabilities and overall well-being of IPV survivors, it is critical that we intentionally focus on developing a better understanding of the nature and consequences of economic abuse.…”
Section: Economic Abusementioning
confidence: 99%
“…Contemporary hegemonic masculinity incorporates several themes, including dominance and violence [ 51 ]. Such themes, as global research reveals, are largely shared among patriarchal societies, and China is no exception [ 52 , 53 , 54 , 55 ]. One Chinese survey that investigated masculine norms and violent behaviors showed that among 1981 participants, 21.8% of female and 52.4% of male respondents agreed that “a man can defend his reputation through violence if he has to” [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such themes, as global research reveals, are largely shared among patriarchal societies, and China is no exception [ 52 , 53 , 54 , 55 ]. One Chinese survey that investigated masculine norms and violent behaviors showed that among 1981 participants, 21.8% of female and 52.4% of male respondents agreed that “a man can defend his reputation through violence if he has to” [ 54 ]. Accordingly, boys raised in such norms learn to behave in corresponding ways through reinforcement and punishment of multiple socializing agents (e.g., family, peers, media, schools).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation